1976
DOI: 10.7589/0090-3558-12.4.516
|View full text |Cite
|
Sign up to set email alerts
|

Response of White-Tailed Deer to Infection With Peste Des Petits Ruminants Virus

Abstract: White-tailed deer (Odocoileus virginianus) were infected experimentally with two strains of peste des petits ruminants virus. The response varied from fatal consequence to subclinical infection. The clinical signs and gross lesions were similar to those in goats. Virus was recovered from all the infected deer, and survivors developed specific antibodies demonstrated by complement fixation and virus neutralization tests. Survivors also resisted challenge with virulent rinderpest virus that was lethal to a contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 2 publications
2
25
0
Order By: Relevance
“…These include high fever up to 42°C, lesions in mouth, oral and nasal congestion, respiratory signs, and diarrhea leading to death of the animals. Similar findings were made in previous reports [9, 15, 16]. In this study it was observed that the morbidity rate was 100% while mortality rate was 31.42%.…”
Section: Discussionsupporting
confidence: 92%
“…These include high fever up to 42°C, lesions in mouth, oral and nasal congestion, respiratory signs, and diarrhea leading to death of the animals. Similar findings were made in previous reports [9, 15, 16]. In this study it was observed that the morbidity rate was 100% while mortality rate was 31.42%.…”
Section: Discussionsupporting
confidence: 92%
“…These include high fever up to 42 o C, lesions in mouth, oral and nasal congestion, respiratory signs and diarrhea leading to death of the animals. Similar findings were made in previous reports (Couacy-Hymann et al, 2007;Hamdy and Dardiri, 1976;Nanda et al, 1996). In the present study it was observed that the morbidity rate was 100% while mortality rate was 31.42%.…”
Section: Samples Collected From Recovered Animalssupporting
confidence: 81%
“…In this study no difference was found, for any of the pathogens, between herds with proximity to wildlife and those without. PPRV has long been known to cause disease in wildlife [28]. Clinical signs are yet to be described in wild ruminants in sub-Saharan Africa, but have been reported in wild ruminants in Asia and in the Middle East [67].…”
Section: Discussionmentioning
confidence: 99%
“…Wild ruminants have been shown to carry PPRV and several species can develop clinical signs of PPR [28,31,32]. Whether interaction or proximity between livestock and wildlife in general, and wild ruminants in particular, is an important risk factor for exposure to PPRV has not yet been determined.…”
Section: Introductionmentioning
confidence: 99%